The Marin Lab at the Dawn of Cognitive Neuropsychology. Issue 3 (September 2015) - Schwartz, Myrna F.
<x xml:space="preserve">Abstract</x> This essay discusses the intellectual developments in psychology, linguistics, and behavioral neurology that shaped Oscar Marin's approach to disorders of high cortical function. As Chief of Neurology at Baltimore City Hospitals in the 1970s, Dr Marin teamed with biopsychologist Eleanor Saffran and the author in seminal studies of acquired language disorders (aphasia) centering on core processes of syntax and semantics, and rejecting premature reductionism. The philosophical and methodological principles that motivated these studies are traced through the author's personal recollections and the published writings of the Marin lab. These principles came to be associated with the cognitive neuropsychology school of research and have important linkages to contemporary work in the neuroscience of aphasia and related cognitive disorders.